The Theology of Solitaire Prosperity: God's Blessings, Restoration, and Channels of Abundance - Yoas Tanugraha; Ruben Nesimnasi (PT FORMOSA CENDEKIA GLOBAL, 2026)
This article examines the dimension of solidarity in charismatic theology by situating the themes of blessing, restoration, and the work of the Holy Spirit within the framework of God’s solidarity with humanity. This study seeks to reconstruct this understanding through the framework of the theology of solidarity, so that prosperity can be interpreted as a holistic restoration of life that also has a social impact. Methodologically, this study is qualitative, combining a constructive theological approach with a literature review of biblical texts, solidarity theology literature, Pentecostal/Charismatic theology, and liberation theology. The research findings reveal that God’s solidarity is manifested through acts of liberation in the Old Testament, reaching its pinnacle in the incarnation, ministry, crucifixion, and resurrection of Jesus Christ, and is subsequently continued through the work of the Holy Spirit, which shapes the church community to live in a spirit of sharing and empowerment.